Biomimetics Linked to Classical Product Development: An Interdisciplinary Endeavor to Develop a Technical Standard - Wanieck, Kristina; Hamann, Leandra; Bartz, Marcel; Uttich, Eike; Hollermann, Markus; Drack, Manfred; Beismann, Heike (Biomimetics, 2022)
Biomimetics is a well-known approach for technical innovation. However, most of its influence remains in the academic field. One option for increasing its application in the practice of technical design is to enhance the use of the biomimetic process with a step-by-step standard, building a bridge to common engineering procedures. This article presents the endeavor of an interdisciplinary expert panel from the fields of biology, engineering science, and industry to develop a standard that links biomimetics to the classical processes of product development and engineering design. This new standard, VDI 6220 Part 2, proposes a process description that is compatible and connectable to classical approaches in engineering design. The standard encompasses both the solution-based and the problem-driven process of biomimetics. It is intended to be used in any product development process for more biomimetic applications in the future.<br
Keywords: innovation; product development; process; solution finding; workflow